2022
DOI: 10.3390/v14020227
|View full text |Cite
|
Sign up to set email alerts
|

Virome Analysis Reveals Diverse and Divergent RNA Viruses in Wild Insect Pollinators in Beijing, China

Abstract: Insect pollinators provide major pollination services for wild plants and crops. Honeybee viruses can cause serious damage to honeybee colonies. However, viruses of other wild pollinating insects have yet to be fully explored. In the present study, we used RNA sequencing to investigate the viral diversity of 50 species of wild pollinating insects. A total of 3 pathogenic honeybee viruses, 8 previously reported viruses, and 26 novel viruses were identified in sequenced samples. Among these, 7 novel viruses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Shi et al ( 5 ) found that numerous and divergent picorna-like viruses were ubiquitous in invertebrate species. In addition, previous virome analyses of honeybees and other insect pollinators also observed that Picornavirale s was the dominant group ( 41 43 ). Furthermore, 46 picorna-like virus sequences were recently identified in multiple marine invertebrate species from three different seas (the South China Sea, the East China Sea, and the Yellow Sea) in China ( 44 ).…”
Section: Discussionmentioning
confidence: 74%
“…Shi et al ( 5 ) found that numerous and divergent picorna-like viruses were ubiquitous in invertebrate species. In addition, previous virome analyses of honeybees and other insect pollinators also observed that Picornavirale s was the dominant group ( 41 43 ). Furthermore, 46 picorna-like virus sequences were recently identified in multiple marine invertebrate species from three different seas (the South China Sea, the East China Sea, and the Yellow Sea) in China ( 44 ).…”
Section: Discussionmentioning
confidence: 74%
“…Another family related to mitoviruses is the Narnaviridae family, which contains nonencapsidated positive-stranded RNA viruses that range from 2.3 to 3.6 kb [87]. We found in our analysis that Ampulexvirus narnaviri clustered with Xiangshan narna-like virus, which was obtained from a mixed pool of several species of insects [88]. It was not possible to classify this species at the genera level since all of the closest species are also defined as unclassified elements within the Narnaviridae family (Figure 3B).…”
Section: Discussionmentioning
confidence: 62%
“…According to the ICTV, Orthomyxoviridae and Xinmoviridae are families of negativesense single-stranded RNA viruses that have been found in insects [81,99]. In particular, orthomyxoviruses are constituted by 6 to 8 segments and have been isolated from insect pollinators in China and Korea [88,100]. Here, we detected two putative orthomyxoviruses composed by five segments (Cotesiavirus orthomyxi and Diachasmavirus orthomyxi) that clustered together.…”
Section: Discussionmentioning
confidence: 81%
“…Genus Formivirus was expanded by one new species, Formivirus pollinis , for Xiāngshān nyami-like virus (XNyV) discovered by metagenomics in wild insect pollinators in Xiāngshān Park (香山公园), Beijing, China [ 24 ] (TaxoProp 2022.016M.A.Nyamiviridae_2nsp).…”
Section: Taxonomic Changes In Subphylum Haploviricotinamentioning
confidence: 99%